Linguistic Aggression and Football Loyalty: A Study of Impoliteness in Twitter Responses to @SpursOfficial - Reliubun, Abdurrahman Shaleh; Dakka, Litha Nesidekawati (Indo-MathEdu Intellectuals Journal, 2025)
This study investigates the use of impoliteness in Twitter responses to the dismissal of Ange Postecoglou by Tottenham Hotspur, despite his recent success in ending the club’s 17-year trophy drought. Using Culpeper’s Impoliteness Theory, 100 reply tweets to the @SpursOfficial announcement were analysed to identify the strategies fans used to express discontent. The data were collected directly from Twitter shortly after the announcement, using purposive sampling. Each tweet was manually coded according to Culpeper’s impoliteness strategies and analysed qualitatively to explore its pragmatic implications. The findings show that bald on-record impoliteness, positive impoliteness, and sarcasm/mock politeness were the most frequently employed strategies. Impoliteness in this context serves both expressive and social functions, allowing fans to signal moral outrage, reject perceived injustice, and reassert their connection to the club. The study highlights the complex role of impoliteness in digital football discourse and its function as a performative act in moments of collective discontent.